The Section 129(1)(a) Notice as a Prerequisite for Debt Enforcement in terms of the National Credit Act 34 of 2005 - Renke, Stefan (University of Pretoria, 2015)
Mini Dissertation (LLM)--University of Pretoria, 2014.